Intrauterine Limb Ischemia in Patient Heterozygous for the 677C>T) RS1801133 (Polymorphism of Methylenetetrahydrofolate Reductase MTHR Gene - Ahmad Al Hammouri; Rami A. Misk; Hamza Abumunshar; Fawzy M. Abunejma; Tasnim S. Idrees; Mahmoud Abu Arqoub; Deiaa Malhis; Abdullah Shroof; Tareq Z. Alzughayyar (Hindawi Limited, 2022)
Background. Intrauterine arterial thrombosis is extremely rare. Multiple inherited coagulopathies were found to be associated with thrombophilia and an increased risk of intrauterine arterial thrombosis. Methylenetetrahydrofolate reductase MTHFR (C667T) polymorphism was found to be associated with mild hyper-homocysteinemia, which, in turn, can promote thrombotic complications. Materials and Methods. We reported a case of intrauterine upper limb ischemia in a neonate who was found to be heterozygous for the 677C > T polymorphism of the MTHFR gene despite the dispute regarding its clinical significance as a risk of arterial thrombosis. We also reviewed the literature and summarized the clinical features, treatment, and prognosis of similar cases. Case Presentation. We reported a full-term female, born by normal spontaneous vaginal delivery who was found to have a swollen, blue left upper limb in the delivery room. Left upper limb computed tomography angiography (CTA) revealed left subclavian artery thrombosis. Investigations for the risk revealed heterozygosity for the MTHFR (C667T) polymorphism. Left upper limb amputation was done after the failure of medical management. Conclusion. Despite the conflict about whether heterozygosity for MTHFR (C667T) polymorphism increases the risk of arterial thrombosis or not, there are few cases in the literature presented with intrauterine upper limb ischemia and were found to be heterozygous for the mutation. We recommend investigating neonates and their parents for complete thrombophilia mutations when they present with unusual vascular occlusion sites as newborns.